The contribution of Paṇḍitarāja Jagannātha to Sanskrit poetics - Śrīrāmacandruḍu, Pullela (New Bharatiya Book Corp., 2008)
Analytical study of Rasagaṅgādhara of Jagannātha Paṇḍitarāja, work on Sanskrit poetics.